Development and Implementation of Junior High School Health Information System in Serang City - Vina Oktiarina; Yayat Ruhiat; Ujang Jamaludin (Postgraduate, University of Mataram, 2024)
The health information system in schools has a crucial function in supporting the implementation of the School Medical (UKS) program. This study aims to evaluate how effective the health information system developed,